2023
DOI: 10.3390/microorganisms11071859
|View full text |Cite
|
Sign up to set email alerts
|

Composite Interventions on Outcomes of Severely and Critically Ill Patients with COVID-19 in Shanghai, China

Abstract: Background: The sixty-day effects of initial composite interventions for the treatment of severely and critically ill patients with COVID-19 are not fully assessed. Methods: Using a Bayesian piecewise exponential model, we analyzed the 60-day mortality, health-related quality of life (HRQoL), and disability in 1082 severely and critically ill patients with COVID-19 between 8 December 2022 and 9 February 2023 in Shanghai, China. The final 60-day follow-up was completed on 10 April 2023. Results: Among 1082 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Nirmatrelvir/ritonavir seems to have a lower probability of improving 2-month survival. 23 Another open-label, multicenter, randomized controlled trial indicated that nirmatrelvir/ritonavir showed no significant reduction in the risk of all-cause mortality on day 28 and the duration of SARS-CoV-2 RNA clearance in which hospitalized adult patients with severe comorbidities. 24 Therefore, patients' critical status may also be responsible for the early favorable antiviral trend and seemingly poor survival outcome of nirmatrelvir/ritonavir in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nirmatrelvir/ritonavir seems to have a lower probability of improving 2-month survival. 23 Another open-label, multicenter, randomized controlled trial indicated that nirmatrelvir/ritonavir showed no significant reduction in the risk of all-cause mortality on day 28 and the duration of SARS-CoV-2 RNA clearance in which hospitalized adult patients with severe comorbidities. 24 Therefore, patients' critical status may also be responsible for the early favorable antiviral trend and seemingly poor survival outcome of nirmatrelvir/ritonavir in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled estimate of nine studies [ 19 , 20 , 27 29 , 32 , 33 , 37 , 38 ] showed a significant difference in mortality rate between patients receiving azvudine and SOC (RR = 0.48, 95% CI: 0.40 to 0.57, P < 0.001, I 2 = 0%, GRADE certainty: moderate) ( Fig 2 ). According to the pooled estimate, seven studies [ 6 , 7 , 25 , 32 , 35 – 37 ] revealed a significant difference in mortality rate between the azvudine and nirmatrelvir-ritonavir groups (RR = 0.73, 95% CI: 0.58 to 0.92, P < 0.05, I 2 = 41%, GRADE certainty: moderate) ( Fig 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of azvudine in reducing COVID-19-related deaths has been the subject of conflicting evidence. While some real-world studies and RCTs have shown a lower risk of death in patients receiving azvudine compared to those receiving SOC/PBO [ 27 ] or nirmatrelvir–ritonavir [ 6 , 32 ], other studies [ 6 , 7 , 25 , 35 ] found no significant differences between azvudine and nirmatrelvir-ritonavir treatments in reducing mortality rates in COVID-19 patients. Conversely, strong evidence supports the effectiveness of nirmatrelvir-ritonavir in reducing the mortality rate related to COVID-19 [ 2 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…These clinical studies were all conducted in China, with 22 published in English and 2 published in Chinese [28,29]. In terms of disease severity, the majority of the included patients in most studies had mild to moderate disease, with four studies including patients with severe to critical illness [14,23,32,33]. Among the analyzed population, one study focused on renal transplant recipients [28], one included individuals with a history of cancer [30], and one study included patients with concomitant cardiovascular disease [31].…”
Section: Search Resultsmentioning
confidence: 99%